2003
DOI: 10.1121/1.1554691
|View full text |Cite
|
Sign up to set email alerts
|

Performance bounds for passive sensor arrays operating in a turbulent medium: Plane-wave analysis

Abstract: The performance bounds of a passive acoustic array operating in a turbulent medium with fluctuations described by a von Kármán spectrum are investigated. This treatment considers a single, monochromatic, plane-wave source at near-normal incidence. A line-of-sight propagation path is assumed. The primary interests are in calculating the Cramer-Rao lower bounds of the azimuthal and elevational angles of arrival and in observing how these bounds change with the introduction of additional unknowns, such as the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…2, 3 Table 1 also includes estimated values for µ that are consistent with the model in (8). The equation for ν in (11) is valid only for sensor separations ρ L eff , where eddy size L eff is tabulated in the rightmost column of Table 1.…”
Section: Modelmentioning
confidence: 84%
See 2 more Smart Citations
“…2, 3 Table 1 also includes estimated values for µ that are consistent with the model in (8). The equation for ν in (11) is valid only for sensor separations ρ L eff , where eddy size L eff is tabulated in the rightmost column of Table 1.…”
Section: Modelmentioning
confidence: 84%
“…The factor κ 1 (weather) depends on the weather conditions as in (8). The spatial coherence γ is determined by ν, the extinction coefficient of the second moment, according to…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…One problem with methods analyzing performance for acoustic sensors (Collier & Wilson, 2003Wilson, 1998) is the large computational cost inherent in using acoustic prediction methods such as the parabolic equation (PE) model to approximate environmental conditions. In Mungiole and Wilson (2006), the authors attempt to overcome the large computational requirements of traditional acoustic TL calculation methods by using an artificial neural network.…”
Section: Introductionmentioning
confidence: 99%
“…Certain types of atmospheric turbulence, namely those related to the wind velocity were determined to be particularly detrimental to DOA estimation performance accuracy. The work of Wilson (1998) was then modified in Collier and Wilson (2003) and Collier and Wilson (2004) for plane waves and spherical waves, respectively. For simple array geometries (lines and rectangles) the authors showed that atmospheric turbulence is extremely important in calculating accurate performance bounds for acoustic arrays.…”
Section: Introductionmentioning
confidence: 99%